Regulatory T Cells Promote Overexpression of Lgr5 on Gastric Cancer Cells via TGF-beta1 and Confer Poor Prognosis in Gastric Cancer - Liu, Xiao-Sun; Lin, Xian-Ke; Mei, Ying; Ahmad, Sabir; Yan, Chong-Xian; Jin, Hai-Long; Yu, Hang; Chen, Chao; Lin, Cai-Zhao; Yu, Ji-Ren (Frontiers in Immunology, 2019)
Background: The leucine-rich repeat containing G protein-coupled receptor 5 (Lgr5) is considered a cancer stem cell marker, and is often overexpressed in tumors. The interaction between Lgr5 and the immune-related tumor microenvironment is not completely understood. The aim of this study was to examine the role of Lgr5 in the microenvironment of gastric cancer (GC), and to explore possible immunological mechanisms influencing Lgr5 expression that are governed by regulatory T cells. Methods: Lgr5 expression was examined in 180 GC tumors by immunohistochemistry, and in 80 pairs of GC tumors for analysis of Th1/Th2 cytokines by ELISA. In addition, SGC7901 cells were co-cultured with patient-derived Tregs, varying concentrations of TGF-β1, TGF-β1 neutralizing antibody, or TGF-β receptor inhibitor SB431542, and Lgr5 and β-catenin expression were examined by qRT-PCR and western blot. Results: In this study, an immunosuppressive microenvironment was associated with high Lgr5 expression in GC. Furthermore, Lgr5 expression was up-regulated in GC cells co-cultured with Tregs or treated with exogenous TGF-β1. This up-regulation was partially inhibited by the TGF-β1 neutralizing antibody, or TGF-β1 receptor antagonist SB431542. β-catenin was up-regulated with high Lgr5 expression induced by exogenous TGF-β1, and this up-regulation was inhibited by SB431542. An increased number of Tregs and high Lgr5 expression in GC tissues were significantly associated with low overall survival. Conclusion: Tregs promoted increased Lgr5 expression in GC cells via TGF-β1 and TGF-β1 signaling pathway, which may involve activation of the Wnt signaling pathway. High Lgr5 expression via TGF-β confer poor prognosis in gastric cancer.